Blood Chemistry Value Assesment in Hypodermatosis of Cattle in the Chechen Republic - Vatsaev, Sh V; Dzhamalova, A Z; Plieva, A M; Baisarova, Z T; Saidulaev, A A (KnE Life Sciences, 2019)
This article is devoted to the problem of cattle hypodermatosis caused by Hypoderma bovis De Geer and Hypoderma lineatum De Villers hypoderma flies. The results of studies of blood chemistry value of cattle diseased with hypodermatosis in the Chechen Republic are revealed in the article. The examination of ten blood samples taken from cattle diseased with animals hypodermatosis showed an increase in the activity of creatinine parameters above normal by 60 % or more, a significant decrease in carotene indicators (within 50 % or more), a relative decrease in crude protein, a decrease in glucose levels, an increase in alkaline phosphatase and alanine-aminotransferase, reduction of the studied reserve alkalinity index vol. % CO2 from 2 to 5 units (12 %) is lower, in six samples an increase in the activity of immunoglobulin IgA. All this is connected with the complex of pathomorphological changes expressed in the mechanical impact – traumatization, intoxication and hypersusceptibility of the organism of the infested animal with the development of inflammatory and dystrophic manifestations associated with injuries of muscle cells and tissues, intoxication, and an acid-alkali balance of the body shift in the acidic side (acidosis), pathological liver abnormality or diseases, with the defeat of organs and body systems, edema in different parts of the body, defect of immunoreaction and homeostasis in the body. Information obtained from biochemical screen provide an opportunity to conduct a deeper assessment of homeostasis and the body’s ability to self-regulate, promptly and comprehensively diagnosing diseases, study the dynamics of the development of pathological processes and conditions in the body, determine the clinical course and justifiably prescribe a complex of effective household and medical-preventive activities aimed at reducing the economic damage to livestock [8, 10].